SEALED WITH TEARS: MATERIAL AND SOCIAL MEANINGS OF A ROYAL LETTER BY COUNTESS PALATINE ANNA (VASA) (1545–1610) - Lahtinen, Anu; Katajamäki, Terhi (Prace Polonistyczne, 2021)
This article offers a case study of how a royal letter can be studied both from verbal and material perspectives. It examines one such letter and the way it reveals personal intentions, and tensions in family relations. Building on their research on the sixteenth-century Swedish letter writing and the Vasa family, the authors give a detailed analysis of Countess Palatine Anna’s (1545–1610) letter from the year 1592, its content and context. The analysis also serves to illustrate the vulnerable position of a consort living far from her family of birth.